Quality of Life Impairment in Bullied Students: A Case Report - Muna, Nailin; Yandri, Hengki (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
Bullying has become a prevalent issue, with widespread media coverage of related incidents. Students' quality of life is important for students who are victims of bullying. The purpose of this study is to analyze the impact of the quality of life of students who are victims of bullying, specifically focusing on the quality of life of students. This study uses a case report research method to describe the quality of life of students who are victims of bullying, the subject of this study is only 1 person, students who experienced bullying were selected based on certain criteria to ensure relevance and suitability for the research objectives. The data of this study was revealed by using structured and in-depth interviews in counseling sessions. Data were collected through thematic analysis, a qualitative analysis method used to identify patterns and themes in the data obtained in the research. The results showed that good physical health, psychological well-being, social relationships, academic achievement, school environment, and emotional well-being can improve quality of life. Future researchers could explore factors that support the recovery of students who are victims of bullying, such as support from family and friends _____________________________________________________________Perundungan telah menjadi masalah yang lazim terjadi, dengan liputan media yang luas terhadap insiden terkait. Kualitas hidup siswa merupakan hal yang penting untuk siswa korban perundungan. Tujuan dari penelitian ini untuk menganalisis dampak kualitas hidup siswa korban bullying, khususnya berfokus pada kualitas hidup siswa. Penelitian ini menggunakan metode penelitian case report untuk mendeskripsikan kualitas hidup siswa korban bullying subjek penelitian ini hanya 1 orang, siswa yang mengalami bullying dipilih berdasarkan kriteria tertentu untuk memastikan relevansi dan kesesuaian dengan tujuan penelitian. Data penelitian ini diungkapkan dengan menggunakan wawancara tertruktur dan mendalam dalam sesi konseling. Data dikumpulkan melalui analisis tematik, sebuah metode analisis kualitatif yang digunakan untuk mengidentifikasi pola dan tema dalam data yang diperoleh dalam penelitian. Hasil penelitian menunjukan bahwa kesehatan fisik, kesejahteraan psikologis,hubungan sosial, prestasi akademik, lingkungan sekolah, dan kesejahteraan emosional yang baik dapat meningkatkan kualitas hidup. Peneliti selanjutnya bisa mengeksplorasi faktor-faktor yang mendukung pemulihan siswa korban bullying, seperti dukungan dari keluarga, dan teman.